Main agronomic traits, domestication and breeding of Gu (Zizania latifolia) - WANG Yingying; HUANG Lu; FAN Longjiang (浙江大学学报. 农业与生命科学版)
Zizania is a cereal species with the closest relationship to Oryza genus in the grass family and is the only genus which is distributed discontinuously between Eurasia and North America in the tribe Oryzeae. Gu (Zizania latifolia) was an important cereal in Chinese history (one of six important cereals in Zhou Dynasty), but it now has disappeared. Another species in Zizania genus, Z. palustris, has been domesticated as a commercial cereal crop in North America in last century. However, no effort has been done in genetic improvement or domestication of Chinese Gu to date.As a part of our effort to recover the ancient Chinese cereal, in this study, the chromosome number of collected Gu was examined by modified carbol fuchsin stain and fluorescent in situ hybridization (FISH). In addition, the main agronomic traits of two sem-i domesticated Gu (Jiayou 1 and Geshan 1) were investigated, including flowering period, inflorescence structure, seed phenotype and germination rate.The results showed that chromosome number of Gu was 2n=34, which was different from that of Z. palustris (2n=30). The flowering period of Jiayou 1 usually happened in one month from the middle of September to October, which was 15 days earlier than wild Gu and 10 days later than Geshan 1. The ratio of pistillate to staminate flowers was about 1∶1.8 and an inflorescence ideograms of Gu was first drawn. The kilo-grain mass of brown Gu was about 12.7 g with 9.70 mm length and 1.48 mm width of brown seeds, which were smaller than Z. palustris. Furthermore, the regular arrangement of starch granules was found in the Gu seed by scanning electron microscope. The germination rate of Jiayou 1 seeds could reach 62.9% with an improved seed treatment method.In sum, the sem-i domesticated Gu, which has a compact plant architecture and normal flowering, provide an important genetic material for the domestication of Gu, although other target traits such as seed shattering need to be improved in future. The ancient crop and its domestication should been given more attention, and more efforts should be taken on artificial mutation breeding.